MODEL PENDIDIKAN NILAI BUDI PEKERTI BERBASIS KEARIFAN LOKAL BAGI SISWA SEKOLAH DASAR - Badeni Badeni; Sri Saparahayuningsih; Agus Makmurtomo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: Model of moral value education based on local wisdom for elementary school education. Purpose of the research was to product the model of moral value education based on local wisdom for elementary school education. Subjects of the research were teachers, elementary students, and Islamic elementary school. Data was collected by interview, observation, documentation, and forum group discussion (FGD). The collected data was analyzed by descriptive qualitative argumentative. Research results showed character education teaching model will effective if it implemented integrally among character education teaching with reflective method, value transformation approach, rational moral cognitive development approach, value analysis approach, value clarification approach, action (habit) teaching approach, and reward and challenge.Keywords: value education model, moral, local wisdom, elementary education Abstrak: Penelitian bertujuan menghasilkan produk model pendidikan nilai budi pekerti berbasis kearifan lokal bagi siswa Sekolah Dasar (SD). Subyek penelitian adalah guru, siswa SD, dan Madrasah Ibtidaiyah (MI). Pengumpulan data melalui interview, observasi, dokumentasi, dan Forum Group Discussion (FGD). Analisis data secara deskriptif kualitatif argumentatif. Hasil penelitian menunjukkan bahwa model pembelajaran pembentukan karakter akan efektif bila dilakukan secara terpadu antara model pembelajaran karakter secara reflektif, pendekatan penanaman nilai, pendekatan pembangunan rasional moral kognitif, pendekatan analisis nilai, pendekatan klarifikasi nilai, pendekatan pembelajaran berbuat (pembiasaan), dan reward and challenge.Kata Kunci: model pendidikan nilai, budi pekerti, kearifan lokal, SD